2010
DOI: 10.1128/jvi.00725-10
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Rep-Associated Factors in Herpes Simplex Virus Type 1-Induced Adeno-Associated Virus Type 2 Replication Compartments

Abstract: Adeno-associated virus (AAV) is a human parvovirus that replicates only in cells coinfected with a helpervirus, such as adenovirus or herpes simplex virus type 1 (HSV-1). We previously showed that nine HSV-1 factors are able to support AAV rep gene expression and genome replication. To elucidate the strategy of AAV replication in the presence of HSV-1, we undertook a proteomic analysis of cellular and HSV-1 factors associated with Rep proteins and thus potentially recruited within AAV replication compartments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
56
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(59 citation statements)
references
References 86 publications
(95 reference statements)
3
56
0
Order By: Relevance
“…MSH2, MSH6, and MLH1 were detected in replication compartments induced by Epstein-Barr virus (10). MSH2, MSH6, and MSH3 were also detected in adenoassociated virus (AAV) replication compartments when HSV-1 was used as the helper virus but not when adenovirus was used as a helper (49). UL12 and ICP8 are also recruited to the AAV replication compartments, and it is possible that they are responsible for the recruitment of MMR proteins (49).…”
Section: Discussionmentioning
confidence: 99%
“…MSH2, MSH6, and MLH1 were detected in replication compartments induced by Epstein-Barr virus (10). MSH2, MSH6, and MSH3 were also detected in adenoassociated virus (AAV) replication compartments when HSV-1 was used as the helper virus but not when adenovirus was used as a helper (49). UL12 and ICP8 are also recruited to the AAV replication compartments, and it is possible that they are responsible for the recruitment of MMR proteins (49).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the strong affinity of RPA32 for single-stranded DNA (102,107) and its function in recruiting the ATRIP-ATR complex to sites of DNA damage (7,26,106), it is not surprising that we and others (65,79) detected RPA32 in HSV-1-supported AAV2 RCs. In HSV-1-infected cells, RPA32 colocalizes with the HSV-1 major single-stranded DNA binding protein ICP8 (81) in HSV-1 RCs (82,93).…”
Section: Discussionmentioning
confidence: 99%
“…Besides viral helper factors, the fate of AAV2 replication also depends on cellular proteins. Recently, cellular proteins have been identified that interact with AAV2 Rep78/68 in adenovirus (Ad)-or HSV-1-supported AAV2 replication (63,65). Of these, the largest functional categories correspond to cellular proteins which are involved in DNA metabolism, including DNA replication, repair, and chromatin modification.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the role of viral exonucleases in DNA replication may be evolutionarily conserved among different dsDNA viruses. In addition, UL12 has been reported to play a role in resolving adeno-associated virus replication intermediates generated when HSV-1 is used as a helper virus (38). Viral and cellular recombination factors may collaborate to mediate viral recombination-dependent replication.…”
Section: Discussionmentioning
confidence: 99%